A new species of Petrocephalus Marcusen 1854 (Osteoglossomorpha: Mormyridae) from the Sanaga River basin, Cameroon - Lavoué, Sébastien (Zootaxa, 2011)
Petrocephalus similis n. sp. is described from the Djerem River, upper Sanaga basin, in Cameroon. It can be distinguished from all other Petrocephalus from West and Central Africa by an unique combination of morphological characters including: body without melanin mark, 22–24 branched rays in the dorsal fin and 28 or 29 branched rays in the anal fin, mouth commissure under the posterior half of the eye. Petrocephalus similis mostly resembles Petrocephalus sullivani. Yet, P. similis has proportionally a larger mouth and a wider head, and reaches a longer maximum standard length. The electric organ discharge waveform of this species is not known. Molecular comparisons based on cytochrome b nucleotide sequences are congruent with morphological comparisons in independently supporting the distinctiveness of this species from 17 other species of Petrocephalus. Within the genus Petrocephalus, P. similis belongs to a group that is almost exclusively composed of endemic species of Central Africa, pointing out its likely origin from this region. Additional examinations of museum specimens from the Sanaga River basin demonstrate the occurrence of at least two other species of Petrocephalus: Petrocephalus microphthalmus, and a second species which is conservatively assigned to Petrocephalus cf. christyi, pending additional evidence.